CAN TEMPERAMENT PREDICT FOREIGN LANGUAGE CLASSROOM EMOTIONS? - To‘lqinova Sevinch O‘tkir qizi (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In the fast-moving modern era, demand and tendency on learning foreign languages especially, English is so greatly growing that people from kindergarten age to adults, even, senior professions in other fields have been making an effort to learn English. Indeed, this is positive situation because language acquisition it not only studies the culture, history and customs of urban-speaking countries, but also opens the success doors in the way of personal interests. This paper is focused on how to acquire the target language without any challenges via knowing the merits of learner’s temperament. Meanwhile, how to formulate lesson procedure with appropriate learning styles and strategies in the sphere of second language acquisition.